The Role of the Tidore Islands City Government in Realizing Legal Protection of Geographical Indications for Puta Dino Kayangan Woven Clothes in Tidore Islands City - Amin Muhammad; Rasty Amalia; Arief Budiono (Dinasti Research, 2025)
The role of the Tidore Islands City government in realizing legal protection of geographical indications for Puta Dino Kayangan woven clothes in Tidore Islands City. Objective: This paper studies the role of the Tidore Islands city government in realizing legal protection of geographical indications for Puta Dino Kayangan woven fabrics in Tidore Islands City. The Puta Dino Kayangan woven fabric is a typical motif woven fabric from Tidore that has not uet been patented, thus requiring legal protection. Methods: This paper employed the empirical research method. The research location is focused on the Puta Dino Weaving House in Soasio Village, Tidore Islands City. Results: Puta Dino woven cloth is a typical Tidore craft product that should receive guidance as regulated in Article 70 of Law No. 20 of 2016 on Trademarks and Geographical Indications, which states that socialization and understanding of the protection of geographical indications and mapping and inventory of potential geographical indication products are carried out by the local Regional Government. Conclusion: This paper serves as an input or a reference material for local governments and related parties in efforts to realize the legal protection of geographical indications of Puta Dino Kayangan woven cloth, and also as input for the community and business actors about the importance of registering geographical indications.